Diallyl Trisulfide Enhances the Survival of Multiterritory Perforator Skin Flaps - Dong, Chengji; Chen, Zhuliu; Zhu, Linxin; Bsoul, Najeeb; Wu, Hongqiang; Jiang, Jingtao; Chen, Xuankuai; Lai, Yingying; Yu, Gaoxiang; Gu, Yanlan; Guo, Xiaoshan; Gao, Weiyang (Frontiers in Pharmacology, 2022)
Multiterritory perforator is one of the widest flap patterns used to repair tissue defects. However, flap necrosis of distal part is still a difficulty for plastic surgeons. Diallyl trisulfide (DATS) is an efficient ingredient extracted from the garlic, exerting many important effects on different disease. Our experiment aims to reveal whether DATS has a beneficial effect on the survival of perforator flaps and to explore the role of autophagy induced by DATS in flaps. The results show that DATS can increase micro-angiogenesis, reduce cell apoptosis and oxidative stress, thereby improving the survival rate of skin flaps. After the addition of autophagy inhibitors, the survival of the flap was further improved. All in all, it is evident that DATS can promote the survival of perforator flaps, which can be enhanced by the inhibition of DATS-induced autophagy.